(3TQM bUjOI GHf GdaGQV GdLjejIs - (3eMeO Hf YHO GdSdGe GdeGdcj GdCRgQis; (3YeQ Hf Ydj Hf GdaGQV GdMehj, CHh MaU,J (B576 (3g` s ((3YHO Gddg Hf YHO GdhGMO Hf YHO GdSdGe GdYHGSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ZQbfG ai HMhQ fYeGFg ahLgJ GdfXQ Edi bUjOJg GdLjejg s
(3BNQgG (B:s
(3hbGd Hf GdScjJ cdeG jfJUH cGdMGFW bjd efg Yhf HGdaJM hGdYhf HGdcSQ eG cGf ai CQV ChOjf hgPG BNQ eG LQi Hg Gdbde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B21s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf ai L(B2 (3U` (B1338 (3Cf GdbUjOI GdMeQjg gi deDdagG YeQ Hf Ydi Hf GdaGQV GdeUQi GdeJhai (B576 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdeLGejYs